Male dyspareunia - Villarreal Valerio, Julián Anibal (2019)
Male dyspareunia is a little known symptom, but with great impact on the quality of life of men who suffer from it. There is little research on this subject compared to its female counterpart. In its etiology there is a wide variety of pathologies with predominance of organic components, so it is important to know and understand the causes for the timely treatment. For the diagnosis of dyspareunia, an adequate history, anamnesis, and physical examination are fundamental to guide its subsequent evolution and management of the disorder through the new treatment options that are currently available, where the individualized approach is useful taking into account other emotional and socio-cultural factors. In this review, an approach is presented on the frequency, diagnosis, evaluation and treatment of this rather complex symptom, which in some cases may have an impact on interpersonal relationships.